Examining the Agreement Object as Good Deeds from the Consequentialism and Deontology Perspective - Taufiq El Rahman (Yustisia Jurnal Hukum, 2021)
This study aimed to analyze the agreement object as good deeds from the legal philosophy perspective. Postulated to legal positivism, this rejects the deviation of the agreement on the good deed of transplanting organs or body tissues. The results compiled using normative legal research methods described the flow of consequentialism and deontology. These doctrines state that kidney transplant procedures conducted voluntarily based on humanity have benefited recipients and donors. Therefore, they increase the happiness level of both parties without leaving the concept of Kantian moral ethics.